The Impact of a Concomitant Meniscus Surgery on Hop Performance Symmetry in Patients Rehabilitating After Anterior Cruciate Ligament Reconstruction - Krishna Malliah; Adam VanZile; Mark Walden; Matthew Pennucci; Adam Botts; Caitlyn Ailor; Scott Ruse; Michael Taylor; Ian Nelson; Matthew Snyder; Daniel Abreu; Emma Yeager; et al. (International Journal of Sports Physical Therapy)
# Background